Challenging Norms and Practices in Women’s Beach Handball: The Bikini Debate - Nathalie Hyde-Clarke; Birgitte Kjos Fonn (Media and Communication, 2024)
Since 1978, the Norwegian Act for Gender Equality has created a strong emphasis on the importance of equality in all parts of society. This implies equal access to all cultural and welfare activities and services—including sports. In the media, we often see strong reactions to examples of discrimination based on gender, such as during the 2021 European Beach Handball Championship, when the Norwegian women’s beach handball team was fined by the European Handball Federation for refusing to play in bikini bottoms during their final matches. Media attention was given to the ensuing international outrage, which included well-known music artist Pink offering to pay on the team’s behalf in a gesture of solidarity. In November 2021, the sport’s International Federation agreed to allow women to compete in a similar uniform to men. This study analyses Norwegian newspaper coverage of the responses from Norwegian women athletes, politicians, and the international sports/media community from July 2021 to March 2022. It also provides an opportunity to determine to what extent the media framed and participated in calls for change.